A STUDY EFFECT OF SOME VARIABLES IN TIG SPOT WELDING FOR (ALUMINUM – MAGNESIUM) ALLOY (Journal of Engineering, 2006)
The present work investigates the effect of some of the variables in spot tungsten inert gas shieldedwelding (TIG Spot) for (Aluminum-Magnesium) alloy type(5052-O) which is non–heat treatablealloy for its wide industrial uses and applications in field of welding technology.TIG Spot welding was performed by using tungsten electrode (EWTh2)of diameter (3.2mm) andDC current with direct polarity (DCSP) at constant shielded gas flow rate (15litre/min).The welded specimens were tested by using the Instron machine to determine the maximum shearforce (shear strength ) of spot welded and to define the optimum conditions of spot weldingvariables in relation to the weld current, weld time and arc length of welding to produce anacceptable weld. The metallurgical changes of the weld zone and heat affected zone were studiedunder optimum conditions of welding.It has been shown that the increase in the welding current and welding time tends to increase themaximum shear force and it reaches maximum value and then decreases with high currents andlong times. The maximum shear force was 2.4KN at welding current of (90) Amp , welding time( 7)sec and arc length (1.6mm ) for 1mm thickness.It was also found that the highest value of hardness ( 53.5 Hv) was at the center of the spot weldedand decreases gradually from the center of the weld spot towards the base metal.